Effective Marketing At Education: Importance of Communication Materials - Terkan, Remziye (International Review of Management and Marketing, 2013)
<!--[if gte mso 9]> 800x600 <![endif]--> Communication is defined as human activities. It is set of circumstances during the people’s lives. Communication is emerged with the emergence of humanity. Communication is production and exchange of meanings verbally, as well as via visual and written materials. Marketing is an exchange processes. Production and design of products & services, pricing, promotion and places are key factors for marketing. Written and visual communications are effective for people in every area. Written and visual communication materials are effective also in marketing, they are like impressive tools and also they are influential for every organization even in higher education in the world. The significance of written and visual communication materials in educational institutions is evaluated in that study. The role and importance of visual and written materials in marketing process of education sector and show communication materials effectiveness on educational institutions achievement is investigated. Keywords: Communication, marketing, communication materials. JEL Classifications: M31 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->